Comparative studies of control system on bldc motors - Multazam, Teuku; Nasution, Fakhruddin Ahmad; Azhar, Fakhri (Jurnal Geuthèë: Penelitian Multidisiplin, 2024)
The research is to compare the performance of the control system on brushless dc motors. The optimization uses Simulink software to obtain value data for the overshoot, rise time and settling time parameters. There are three control methods used in this comparative optimization study, namely, a controller system using PID, Cohen-Coon, trial and error, and the Firefly algorithm. The simulation results show that the PID controller optimized using the Firefly algorithm has the best performance with overshoot of 0.501%, rise time of 234,778 ms, and settling time of 0.6. The Cohen-Coon method also produces low overshoot of 0.501%, but with a longer rise time of 234,778 ms and a higher settling time. This study found that to improve control system performance, it is very important to choose the right optimization technique. When compared with the Cohen-Coon and Trial and Error methods, the Firefly algorithm shows better results in determining the most suitable parameters for PID controllers on BLDC motors. These findings provide important guidelines for the development and use of PID controllers in various industries using BLDC motors.